Complementary feeding, dietary diversity, and diarrhea morbidity in some rice-growing regions of Kenya: insights for targeted nutrition interventions - Diba, Halima; Odingo, Sylvia Kavai; Juma, Rose Janet; Ouna, Benard Aswani; Mapesa, Job (World Nutrition, 2025)
BackgroundDiarrhea and malnutrition remain major contributors to child morbidity and mortality in Kenya, particularly among children under five. Inadequate complementary feeding, poor dietary diversity, and weak hygiene practices exacerbate these risks, especially in rural, food insecure areas. In several rice-growing regions in Kenya, disparities in food access, caregiver practices, and sanitation contribute to nutritional inequality and a higher disease burden among young children.ObjectiveTo assess in selected rice-growing counties in Kenya factors that can affect child nutrition, including complementary feeding practices, diarrhea incidence and management, and household dietary diversity.MethodsA cross-sectional survey was conducted among 1,218 households with children aged 6–59 months in Kirinyaga, Kisumu, and Kwale counties. Data on socio-demographic characteristics, feeding practices, hygiene behaviors, diarrhea morbidity, and dietary diversity were collected through structured interviews. Descriptive and inferential statistics, including chi-square tests, were used for analysis.ResultsComplementary feeding was introduced at six months in 76.5% of households, with significant differences across counties (p=0.007). Feeding frequency was notably suboptimal in Kwale, where 50.7% of caregivers fed children only twice a day or less. Diarrhea morbidity affected 28.4% of children overall, with the highest incidence reported in Kwale (36.7%, p=0.001). Household dietary diversity score (HDDS) also showed significant variation, with 19.7% of households falling into the low HDDS category.ConclusionsThe study reveals regional variations in feeding practices, hygiene behaviors, and dietary diversity that contribute to childhood diarrhea and malnutrition. Targeted interventions, focusing on nutrition education, improved water, sanitation, and hygiene practices, and food-based strategies such as reintegrating nutrient-rich rice bran, are essential to address underlying inequalities and improve child health outcomes in these rice growing regions.